Recreational exercise is associated with lower prevalence of depression and anxiety and better quality of life in German people living with HIV. Issue 2 (1st February 2022) - Pérez-Chaparro, Camilo; Kangas, Maria; Zech, Philipp; Schuch, Felipe B.; Rapp, Michael; Heissel, Andreas
ABSTRACT: Sedentarism is a risk factor for depression and anxiety. People living with the human immunodeficiency virus (PLWH) have a higher prevalence of anxiety and depression compared to HIV-negative individuals. This cross-sectional study ( n = 450, median age 44 (19–75), 7.3% females) evaluates the prevalence rates and prevalence ratio (PR) of anxiety and/or depression in PLWH associated with recreational exercise. A decreased likelihood of having anxiety (PR=0.57; 0.36-0.91; p = 0.01), depression (PR=0.41; 0.36-0.94; p =0.01), and comorbid anxiety and depression (PR = 0, 43; 0.24-0.75; p =0.002) was found in exercising compared to non-exercising PLWH. Recreational exercise is associated with a lower risk for anxiety and/or depression. Further prospective studies are needed to provide insights on the direction of this association.